Utilization of ROS in Human Support Robot (HSR) - Chandran, Livenesh; Hazwaj Mhd Poad (Evolution in Electrical and Electronic Engineering, 2022)
Robots have played a big part in our lives and can be utilized through numerous methods currently in the world. Robots without understanding simple instructions may be a problem for users who are currently using and running robots in their lifetime. In this project, the main focus will be mostly on the virtual robot which is the HSR Robot (Home Service Robot), and how to control it fully online. This project will mostly use the software Unity 3D and ROS Noetic as its core mechanics in helping the task of correctly controlling the robot through virtual means. At the end of this project, the virtual robot should be able to understand basic instructions imputed and controlled by the user. The result of the experiments is explained in this paper.